Causes, Consequences and Counselling Strategies for Managing Lateness among Secondary School Students in Awka Education Zone, Anambra State - Francisca; Gloria; ilo; Chioma; IJ; Mohammed (Journal of Research in Industrial Technology and Educational Studies, 2026)
Lateness to school among secondary school students has become a persistent behavioural challenge affecting academic performance, classroom management, and school discipline in Nigeria, particularly in Awka South Local Government Area of Anambra State. This study investigated the causes, consequences and counselling strategies for managing secondary school students' lateness to school in Awka Education Zone of Anambra State. A descriptive survey design was adopted. The study population comprised all 65 school counsellors in public secondary schools across the five Local Government Areas in Awka Education Zone; including Awka North, Awka South, Aniocha, Njikoka and Dunukofia. Census sampling was adopted and all 65 counsellors served as the study sample. Data were collected using a structured questionnaire validated by experts in Educational Psychology and Guidance and Counselling. Reliability was established using Cronbach’s Alpha with acceptable coefficient of 0.78. Data were analyzed using mean and standard deviation. Findings revealed that lateness is caused by poor parental supervision, peer influence, distance to school, weak self-discipline, environmental challenges, and lack of motivation. The consequences include poor academic performance, disruption of classroom instruction, indiscipline, reduced instructional time, and strained teacher student relationships. Counselling strategies such as self-management techniques, behavioural modification, group counselling, and parental involvement were found effective in managing lateness. The study concludes that lateness is a multi-dimensional behavioural problem requiring integrated counselling and school-based interventions. It recommends strengthening school counselling services and adopting behavioural intervention programmes in secondary schools.
Keywords: Lateness; Secondary school studenrs; Counselling strategies; Behaviour management; Awka education Zone